Properties and pulsed current activated consolidation of nanostuctured MgSiO3-MgAl2O4 composites - Shon, In-Jin; Du, Song-Lee; Doh, Jung-Mann; Yoon, Jin-Kook (KOREAN INST METALS MATERIALS, 2013)
Nanocrystalline materials have received much attention as advanced engineering materials with improved physical and mechanical properties. As nanomaterials possess high strength, high hardness, excellent ductility and toughness, undoubtedly, more attention has been paid for the application of nanomaterials. Nanopowders of MgO, Al2O3 and SiO2 were made by high energy ball milling. The simultaneous synthesis and consolidation of nanostuctured MgAl2O4-MgSiO3 composites from milled 2MgO, Al2O3 and SiO2 powders was investigated by the pulsed current activated sintering process. The advantage of this process is that it allows very quick densification to near theoretical density and inhibition of grain growth. Highly dense nanostructured MgAl2O4-MgSiO3 composites were produced with a simultaneous application of 80 MPa pressure and a pulsed current of 2000A within 1min. The fracture toughness of MgAl2O4-Mg2SiO4 composites sintered from 60 mol%MgO-20 mol%Al2O3-20mol%SiO2 powders milled for 4 h was 3.2MPa center dot m(1/2). The fracture toughness of MgAl2O4-MgSiO3 composite is higher than that of monolithic MgAl2O4.
Keywords: MECHANICAL-PROPERTIES; FABRICATION